Jesus Christ (p.b.u.h) beloved Prophet of Islam - Deedat, Ahmed; Saba Islamic Media ([Kuala Lumpur] : Saba Islamic Media)
Lecture at Tuscon, Arizona on 5th November 1986. In this lecture, Sheikh Ahmed Deedat shows what Islam says about Jesus (peace be upon him). Explain the great status Jesus (pbuh) is given in Islam as well as his true nature, a great prophet of God or God himself
Title from title screen
Speaker: Sheikh Ahmed Deedat
Keywords: Jesus Christ; Jesus Christ -- Islamic interpretations